The Production of Organic Matter from Rhizophora mucronata and Sonneratia alba at The Kajhu and Meunasah Mesjid Villages, Aceh Besar - Mai Suriani; Dietriech G Bengen; Tri Prartono (Journal Omni-Akuatika, 2017)
Production and decomposition of mangrove litter could contribute organic matter and nutrients to the coastal waters. This study was to estimate the extent to which the rehabilitated mangrove of Rhizophora mucronata and Sonneratia alba contribute organic matter. This study was conducted from November 2015 to January 2016. Litter traps were used to collect the litter production and litterbags to measure decomposition rates. The results showed that the average of litter production for Sonneratia alba and Rhizophora mucronata was 4,38 g.m-2.day-1 and 3,61 g.m-2.day-1, respectively. However, Sonneratia alba apparently showed higher decay rates compare with Rhizophora mucronata. Nutrients element (N and P) released were 321,2 kg.ha-1.years-1 and 47,45 kg.ha-1.years-1 for Sonneratia alba; and 131,4 kg.ha-1.years-1 and 13,14 kg.ha-1.years-1 for Rhizophora mucronata. Overall, this study indicated that the mangrove rehabilitation in the area study contributed insignificantly carbon restocking the affected area, although it was able to provide ecological functions of this mangrove ecosystem.